Perioperative Alanyl‐Glutamine–Supplemented Parenteral Nutrition in Chronic Radiation Enteritis Patients With Surgical Intestinal Obstruction: A Prospective, Randomized, Controlled Study. (15th June 2015) - Yao, Danhua; Zheng, Lei; Wang, Jian; Guo, Mingxiao; Yin, Jianyi; Li, Yousheng
Abstract : Background: A prospective, randomized, controlled study was performed to evaluate the effects of perioperative alanyl‐glutamine–supplemented parenteral nutrition (PN) support on the immunologic function, intestinal permeability, and nutrition status of surgical patients with chronic radiation enteritis (CRE)–induced intestinal obstruction. Methods: Patients who received 0.4 g/kg/d alanyl‐glutamine and isonitrogenous PN were assigned to an alanyl‐glutamine–supplemented PN (Gln‐PN) group and a control group, respectively. Serum levels of alanine aminotransferase and glutamine, body fat mass (FM), immunologic function, and intestinal permeability were measured before and after surgery. Results: Serum glutamine levels of the Gln‐PN group significantly exceeded that of the control group ( P < .001; Gln‐PN, baseline 460.7 ± 42.5 vs 523.3 ± 48.6 µmol/L on postoperative day 14 [POD14], P < .001; control, baseline 451.9 ± 44.0 vs 453.8 ± 42.3 µmol/L on POD14, P = .708). Lactulose/mannitol ratios of both groups decreased over time (Gln‐PN, baseline 0.129 ± 0.0403 vs 0.024 ± 0.0107 on POD1 4; control, baseline 0.125 ± 0.0378 vs 0.044 ± 0.0126 on POD14, P < .001 in both groups). CD4/CD8‐positive T‐lymphocyte ratios significantly rose in both groups, with significant intergroup difference ( P < .001; Gln‐PN, baseline 1.36 ± 0.32 vs 1.82 ± 0.30 on POD14, P < .001; control, baseline 1.37 ± 0.25 vs 1.63 ± 0.31 on POD14, P < .001). In the Gln‐PN group, FM increased from 3.68 ± 1.68 kg at baseline to 5.22 ± 1.42 kg on POD14 ( P < .001). FM of control group increased from 3.84 ± 1.57 kg at baseline to 5.40 ± 1.54 kg on POD14 ( P < .001). However, there were no significant intergroup differences ( P = .614). Conclusion: Gln‐PN significantly boosted the immune state and decreased the intestinal permeability of CRE patients. However, Gln‐PN was not superior to standard PN in improving the nutrition state and intestinal motility of surgical patients with CRE‐induced intestinal obstruction.